Pengaruh Kompetensi dan Pelatihan Terhadap Prestasi Kerja Pegawai pada Kantor Samsat Kota Bima - Gita Gutawa; Firmansyah Kusumayadi; Sugeng Wikakdo (Indo Publishing, 2026)
This study aims to examine the influence of competence and training on employee job performance at the Bima City Samsat Office. Improving the quality of human resources is essential for enhancing organizational performance, particularly in public service institutions that are required to deliver effective, efficient, and professional services. This study employed a quantitative approach with an associative research design. The population consisted of 42 employees of the Bima City Samsat Office, all of whom were selected as the research sample using the saturated sampling (total sampling) technique. Data were collected through questionnaires, observations, and literature review. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination (R²), t-test, and F-test with the assistance of SPSS software. The results indicate that all research instruments were valid and reliable and met the classical assumption requirements. The multiple linear regression equation obtained was Y = 5.449 + 0.500X₁ + 0.222X₂ + e. The partial test revealed that competence had a positive and significant effect on employee job performance (t = 4.337; p = 0.000 < 0.05), whereas training did not have a significant effect (t = 1.797; p = 0.080 > 0.05). However, the simultaneous test demonstrated that competence and training jointly had a positive and significant effect on employee job performance (F = 16.043; p = 0.000 < 0.05). The coefficient of determination (R² = 0.451) indicates that competence and training explained 45.1% of the variation in employee job performance, while the remaining 54.9% was influenced by other factors not examined in this study. Therefore, it can be concluded that competence is a key factor in improving employee job performance, while the implementation of training programs should be evaluated and optimized to better support employee performance improvement.